Farming, forest and savanna in western Nigeria - Morgan, W. B.; Moss, R. P. (ERDKUNDE, 1970)
The study shows the interaction of economic and ecological site factors on land use in the transition area between forest and savannah in western Nigeria. On their own, neither the economic nor the ecological location factors can satisfactorily explain the observed conditions. A similar interaction is probably characteristic of large parts of this zone in West Africa. If the biological properties of this zone are to be used effectively, then further studies in similar areas must be carried out. The results show that the simple but common distinction between forest and savannah agriculture does not hold in this area, even though the natural bases of agriculture so conceptualized influence the economic factors to a significant extent. However, their mode of operation can only be understood in the context of the economic and general economic conditions of the area, not least because it is influenced by the presence of larger cities with their need for food and fuel.